Caspian region: The geopolitical implications for European energy strategy - Ulviyye Aydin; Dina Azhgaliyeva (Asian Development Bank Institute (ADBI), 2019)
Following the collapse of the Soviet Union, Western countries have signed several agreements regarding the use of hydrocarbon resources in the Caspian Basin, with the aim of diversifying their energy suppliers. However, recession in the world economy and persistently low oil prices have profoundly affected the economies of the Caspian states, whose gross domestic product and exports are dominated by oil and oil products. Strongly dependent on export revenues from oil and gas, the economic growth of these states has slowed since 2014. Although limited energy resources have stimulated an emphasis on security of supply, fundamentally understood as a continued and low-risk strategy of interruption of energy import flows, low oil prices have also maintained focus on the challenge of security of demand faced by energy-producing economies in terms of stable energy export revenues. However, geopolitical developments around the world, especially local armed conflicts, highlight the importance of secure routes, as they present a threat to energy transportation. Using an indicator-based approach and country-level data over the period 2000−2017, this paper assesses the security of demand for the oil and gas of three countries in the Caspian region: Azerbaijan, Kazakhstan, and Turkmenistan, over a 16-year period, capturing the geopolitical situation and contributing to a greater understanding of the impact of energy-transporting countries' geopolitical situation on energy transportation to the European Union (EU). The results demonstrate that risk of energy security of demand is greater when political risk in energy-transporting countries is included within a measure of energy security of demand, i.e., risky external energy demand. The sharp decline in political stability and absence of violence or terrorism ratings in Ukraine and Turkey has increased the risk of security of energy demand in Azerbaijan, Kazakhstan, and Turkmenistan. The results highlight the importance of cooperation not only between the EU and the Caspian region, but also with energy-transporting countries, such as Ukraine, Georgia, and Turkey. Alternatively, routes may be found that bypass countries with low levels of political stability, such as through the Trans-Caspian Pipeline.
Keywords: Q32; Q35; Q41; O13; 330; energy security; energy-transporting countries; crude oil export; natural gas export; security of demand